A method for preparing antimony-free environmentally friendly flame-retardant PET polyester

By adding DOPO/phosphorhrode -containing polyacrylate nuclear shell flame retardant mother particles to PET polyester, the pre -emulsified semi -continuous seed emulsion aggregation method is used to obtain nano -grade flame retardant female granules, which solves the conventional PET polyester flammable and flame retardant Environmental health issues have achieved efficient flame retardant and mechanical performance.

CN118580650BActive Publication Date: 2025-01-28SUQIAN YIDA NEW MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410773437.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-17
Publication Date
2025-01-28
Estimated Expiration
2044-06-17

AI Technical Summary

Technical Problem

Conventional PET polyester is flammable, has a low limit oxygen index, and is prone to dripping during combustion, which limits its application. Existing flame retardants such as halogen antimony synergistic flame retardants and organic phosphoric acid derivatives have environmental and health problems, and Poor capacity affects material performance.

Method used

By adding DOPO/phosphoric polyacrylate nuclear shell flame retardant parent particles, the pre -emulsified semi -continuous seed emulsion aggregation method is used to obtain nano -grade flame retardant mother particles to improve the anti -melting performance and flame retardant effect of PET polyester, and through nano Enhance effects to improve mechanical properties, and avoid the use of brine coordinating flame retardants.

Benefits of technology

It significantly improves the flame retardant performance and mechanical properties of PET polyester, avoids the negative effects of coordinated flame retardants on the environment and health, and improves the anti -melting drop performance and oxygen index of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an antimony-free and environment-friendly flame-retardant PET polyester and a preparation method thereof. DOPO / phosphorus-containing polyacrylate core-shell flame-retardant masterbatch is added to improve the anti-melting droplet performance and the flame-retardant effect of the PET polyester. Meanwhile, a nano-scale DOPO / phosphorus-containing polyacrylate core-shell flame-retardant masterbatch is prepared by a pre-emulsified semi-continuous seed emulsion polymerization method, so as to exert a nano-enhancement effect and improve the mechanical properties of the PET polyester.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardant materials, and particularly relates to a method for preparing antimony-free, environment-friendly flame retardant PET polyester. Background Art

[0002] Engineering plastics are widely used in aerospace, automotive, electrical and electronic, machinery and other industries due to their excellent mechanical properties, heat resistance, dimensional stability and electrical insulation. Polyethylene terephthalate (PET) is an excellent engineering plastic with excellent mechanical properties (such as tensile strength, fatigue resistance, compressive strength), high temperature resistance and environmental friendliness. It has received extensive attention and applications in aerospace, mechanical devices, high-speed rail, ships, automobiles, building insulation and other fields. However, the flammable nature of conventional PET, with a limiting oxygen index of only 21, and it is very easy to drip during combustion, which can easily cause secondary combustion, limiting its application.

[0003] The methods for improving the flame retardant properties in the prior art mainly include adding flame retardants to polyester compositions and adding flame retardant monomers to the in-situ polymerization of polyesters. However, in-situ polymerization addition is limited to specific polyester products and cannot be widely used. Adding flame retardants has more convenient and flexible application characteristics and has a wider application. Commonly used additive flame retardants mainly include inorganic flame retardants and organic flame retardants. Halogen antimony synergistic flame retardants are common inorganic flame retardants with the advantages of stable flame retardant properties, high flame retardant efficiency and low price, but they will produce corrosive gases and smoke, causing problems to the environment and health, and due to poor compatibility with polyester matrix, it is easy to cause its tensile strength and other mechanical properties to crack. As an organic flame retardant, organic phosphoric acid derivatives also have good flame retardant properties by improving the carbonization performance of the material. In recent years, they have received more and more attention and have higher environmental and health friendliness, but in terms of flame retardancy, there is a problem that it is easy to seep out when heated, and it is generally in liquid state and difficult to handle, which leads to the problem that it is easy to drip when used as a flame retardant modified polyester. Summary of the invention

[0004] In order to overcome the above-mentioned defects, the purpose of the present invention is to provide a method for preparing antimony-free, environmentally friendly flame-retardant PET polyester, by adding DOPO / phosphorus-containing polyacrylate core-shell flame-retardant masterbatch to improve the anti-dripping performance and flame retardant effect of PET polyester, and at the same time, a nano-scale DOPO / phosphorus-containing polyacrylate core-shell flame-retardant masterbatch is prepared by a pre-emulsified semi-continuous seed emulsion polymerization method to exert a nano-enhancement effect and improve the mechanical properties of PET polyester.

[0005] The present invention provides a DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch, and the preparation method thereof comprises the following steps:

[0006] Step 1, add 1-10 g of N-(3-aminopropyl)methylacrylamide hydrochloride and 5-45 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to xylene, react at a temperature of 100-120° C. for 30-50 hours, concentrate the reaction solution, wash with sodium bicarbonate aqueous solution and acetone in sequence, and dry to obtain DOPO-aminopropylacrylamide intermediate;

[0007] Step 2, adding 5-25 g of DOPO-aminopropyl acrylamide intermediate and 1-10 g of olefinic acid to xylene, reacting at a temperature of 25-45° C. for 1-3.5 h, concentrating the reaction solution, washing with acetone and ethanol in turn, and drying to obtain modified DOPO;

[0008] Step 3, dissolve 0.1-5g SDS in water to form 100mL-500mL of aqueous phase, add 1-20g of modified DOPO, 1-20g of methyl methacrylate, and 0.01-0.1g of AIBN to 100mL-500mL of acetone to form oil phase 1, 3-30g of methyl methacrylate, 3-30g of styrene, 1-20g of polyphosphorylcholine glycol acrylate, 3-30g of isooctyl acrylate, and 0.1-0.9g of AIBN to 200mL-700mL of acetone to form oil phase 2, add oil phase 1 to the aqueous phase, stir and emulsify to form an oil-in-water emulsion, introduce nitrogen, heat to 70-85°C with stirring and react for 1-2h to form a core layer, continue to drop oil phase 2, drop it within 2-5h to form a shell layer, cool to room temperature, filter, and wash to obtain DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch.

[0009] Preferably, the particle size of the DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch is 20-150 nm.

[0010] Preferably, step 1 comprises 3-10 g of N-(3-aminopropyl)methacrylamide hydrochloride and 10-35 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0011] Preferably, the olefinic acid in step 2 comprises one or more of maleic anhydride, itaconic acid and acrylic acid.

[0012] Preferably, the olefinic acid in step 2 is maleic anhydride.

[0013] Preferably, step 2 comprises 10-20 g of DOPO-aminopropylacrylamide intermediate and 2-6 g of olefinic acid.

[0014] Furthermore, the present invention provides an antimony-free, environment-friendly flame-retardant PET polyester, which includes 100 parts of PET polyester, 10-30 parts of glass fiber, 2-12 parts of silane coupling agent, 3-8 parts of DOPO / phosphorus-containing polyacrylate core-shell flame-retardant masterbatch and 1-10 parts of antioxidant 1010.

[0015] Preferably, an antimony-free, environmentally friendly flame-retardant PET polyester comprises 100 parts of PET polyester, 25 parts of glass fiber, 5 parts of silane coupling agent, 6 parts of DOPO / phosphorus-containing polyacrylate core-shell flame-retardant masterbatch and 3 parts of antioxidant 1010.

[0016] Furthermore, the present invention provides a method for preparing antimony-free environmentally friendly flame-retardant PET polyester, the preparation method comprising the following steps:

[0017] Step S1: weigh the raw materials.

[0018] Step S2: In a high-speed mixer, first add glass fiber and silane coupling agent and mix for 5 minutes, then add PET polyester, DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch and antioxidant 1010 and mix for 10 minutes.

[0019] Step S3: adding the mixed materials in step 2 into an extruder, setting the temperature of each section of the extruder to 230° C.-270° C., and extruding to obtain antimony-free, environment-friendly, flame-retardant PET polyester masterbatch.

[0020] The beneficial effects of the present invention are:

[0021] 1. The self-made DOPO / phosphorus-containing polyacrylate core-shell flame-retardant masterbatch of the present invention uses olefinic acid to pre-treat and modify DOPO to make it reactive and able to copolymerize with acrylate monomers through chemical bonds. The core layer includes a reactive flame-retardant monomer DOPO and the shell layer includes a reactive flame-retardant monomer polyphosphorylcholine glycol acrylate. The anti-dripping performance and flame-retardant effect of PET polyester are improved through the synergistic effect of the two reactive flame-retardant monomers.

[0022] 2. Nano-scale core-shell flame-retardant masterbatch is prepared by pre-emulsification semi-continuous seed emulsion polymerization to exert nano-enhancement effect and improve the mechanical properties of PET polyester.

[0023] 3. By using homemade DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch to improve the flame retardancy of PET polyester and avoid the use of halogen antimony synergistic flame retardants, the environmental and health friendliness can be improved. DETAILED DESCRIPTION

[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The present invention is further explained below in conjunction with specific implementation modes.

[0026] Preparation Example 1 Preparation of DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch

[0027] Step 1, add 5 g of N-(3-aminopropyl)methyl acrylamide hydrochloride and 8 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 100 mL of xylene, react at a temperature of 110° C. for 36 hours, concentrate, wash with sodium bicarbonate aqueous solution and acetone in sequence, and dry to obtain DOPO-aminopropyl acrylamide intermediate;

[0028] Step 2, adding 6.5 g of DOPO-aminopropylacrylamide intermediate and 5 g of maleic anhydride to 100 mL of xylene, reacting at 30° C. for 2 h, concentrating, washing with acetone and ethanol in sequence, and drying to obtain DOPO-maleic anhydride;

[0029] Step 3, 0.5g SDS is dissolved in 500mL water to form an aqueous phase, 3.5g DOPO-maleic anhydride, 2.5g methyl methacrylate, 0.05g AIBN are added to 100mL acetone to form oil phase 1, 5g methyl methacrylate, 3.5g styrene, 3.5g polyphosphorylcholine glycol acrylate, 4.5g isooctyl acrylate, 0.15g AIBN are added to 200mL acetone to form oil phase 2, oil phase 1 is added to the aqueous phase, stirred and emulsified to form an oil-in-water emulsion, nitrogen is introduced, and the temperature is raised to 75°C under stirring for 1.5h to form a core layer, and oil phase 2 is continued to be dripped, and the dripping is completed within 3h to form a shell layer, cooled to room temperature, filtered, and washed to obtain DOPO-maleic anhydride / phosphorus-containing polyacrylate core-shell flame retardant masterbatch. After testing, the particle size is 68nm.

[0030] Preparation Example 2 Preparation of DOPO / polyacrylate core-shell flame retardant masterbatch

[0031] Step 1, add 5 g of N-(3-aminopropyl)methyl acrylamide hydrochloride and 8 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 100 mL of xylene, react at a temperature of 110° C. for 36 hours, concentrate, wash with sodium bicarbonate aqueous solution and acetone in sequence, and dry to obtain DOPO-aminopropyl acrylamide intermediate;

[0032] Step 2, adding 6.5 g of DOPO-aminopropylacrylamide intermediate and 5 g of maleic anhydride to 100 mL of xylene, reacting at 30° C. for 2 h, concentrating, washing with acetone and ethanol in sequence, and drying to obtain DOPO-maleic anhydride;

[0033] Step 3, 0.5g SDS is dissolved in 500mL water to form an aqueous phase, 3.5g DOPO-maleic anhydride, 2.5g methyl methacrylate, 0.05g AIBN are added to 100mL acetone to form oil phase 1, 5g methyl methacrylate, 7g styrene, 4.5g isooctyl acrylate, 0.15g AIBN are added to 200mL acetone to form oil phase 2, oil phase 1 is added to the aqueous phase, magnetic stirring emulsification is performed to form an oil-in-water emulsion, nitrogen is introduced, and the temperature is raised to 75°C under stirring for 1.5h to form a core layer, and oil phase 2 is continued to be added dropwise, and the dropwise addition is completed within 3h to form a shell layer, cooled to room temperature, filtered, and washed to obtain DOPO-maleic anhydride / polyacrylate core-shell flame retardant masterbatch. After testing, the particle size is 93nm.

[0034] Preparation Example 3 Preparation of DOPO / phosphorus-containing polyacrylate flame retardant masterbatch

[0035] Step 1, add 5 g of N-(3-aminopropyl)methyl acrylamide hydrochloride and 8 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 100 mL of xylene, react at a temperature of 110° C. for 36 hours, concentrate, wash with sodium bicarbonate aqueous solution and acetone in sequence, and dry to obtain DOPO-aminopropyl acrylamide intermediate;

[0036] Step 2, adding 6.5 g of DOPO-aminopropylacrylamide intermediate and 5 g of maleic anhydride to 100 mL of xylene, reacting at 30° C. for 2 h, concentrating, washing with acetone and ethanol in sequence, and drying to obtain DOPO-maleic anhydride;

[0037] Step 3, 0.5g SDS is dissolved in 500mL water to form an aqueous phase, 3.5g DOPO-maleic anhydride, 2.5g methyl methacrylate, 5g methyl methacrylate, 3.5g styrene, 3.5g polyphosphorylcholine glycol acrylate, 4.5g isooctyl acrylate, and 0.15g AIBN are added to 300mL acetone to form an oil phase, and the oil phase is added to the aqueous phase, magnetically stirred and emulsified to form an oil-in-water emulsion, nitrogen is introduced, and the temperature is raised to 75°C under stirring for 3.5h, cooled to room temperature, filtered, and washed to obtain DOPO-maleic anhydride / phosphorus-containing polyacrylate flame retardant masterbatch. After testing, the particle size is 0.9um.

[0038] Preparation Example 4 Preparation of DOPO / phosphorus-containing polyacrylate flame retardant masterbatch

[0039] 0.5g SDS was dissolved in 500mL water to form an aqueous phase, 3.5g DOPO, 2.5g methyl methacrylate, 5g methyl methacrylate, 3.5g styrene, 3.5g polyphosphorylcholine glycol acrylate, 4.5g isooctyl acrylate, and 0.15g AIBN were added to 300mL acetone to form an oil phase, and the oil phase was added to the aqueous phase, magnetically stirred and emulsified to form an oil-in-water emulsion, nitrogen was introduced, and the temperature was raised to 75°C under stirring for 3.5h, cooled to room temperature, filtered, and washed to obtain DOPO / phosphorus-containing polyacrylate flame retardant masterbatch. After testing, the particle size was 2.1um.

[0040] Example 1

[0041] Step S1: weigh 100 parts of PET polyester, 25 parts of glass fiber, 5 parts of silane coupling agent, 6 parts of DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch prepared in Preparation Example 1 and 3 parts of antioxidant 1010.

[0042] Step S2: In a high-speed mixer, first add glass fiber and silane coupling agent and mix for 5 minutes, then add PET polyester, DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch prepared in Preparation Example 1 and antioxidant 1010, and mix for 10 minutes.

[0043] Step S3: adding the mixed materials in step 2 into an extruder, setting the temperature of each section of the extruder to 230° C.-270° C., and extruding to obtain antimony-free, environment-friendly, flame-retardant PET polyester masterbatch.

[0044] Comparative Example 1

[0045] Step S1: weigh 100 parts of PET polyester, 25 parts of glass fiber, 5 parts of silane coupling agent, 6 parts of DOPO / polyacrylate core-shell flame retardant masterbatch prepared in Preparation Example 2 and 3 parts of antioxidant 1010.

[0046] Step S2: In a high-speed mixer, first add glass fiber and silane coupling agent and mix for 5 minutes, then add PET polyester, DOPO / polyacrylate core-shell flame retardant masterbatch prepared in Preparation Example 2 and antioxidant 1010, and mix for 10 minutes.

[0047] Step S3: adding the mixed materials in step 2 into an extruder, setting the temperature of each section of the extruder to 230° C.-270° C., and extruding to obtain antimony-free, environment-friendly, flame-retardant PET polyester masterbatch.

[0048] Comparative Example 2

[0049] Step S1: weigh 100 parts of PET polyester, 25 parts of glass fiber, 5 parts of silane coupling agent, 6 parts of DOPO / phosphorus-containing polyacrylate flame retardant masterbatch prepared in Preparation Example 3 and 3 parts of antioxidant 1010.

[0050] Step S2: In a high-speed mixer, first add glass fiber and silane coupling agent and mix for 5 minutes, then add PET polyester, DOPO / phosphorus-containing polyacrylate flame retardant masterbatch prepared in Preparation Example 3 and antioxidant 1010, and mix for 10 minutes.

[0051] Step S3: adding the mixed materials in step 2 into an extruder, setting the temperature of each section of the extruder to 230° C.-270° C., and extruding to obtain antimony-free, environment-friendly, flame-retardant PET polyester masterbatch.

[0052] Comparative Example 3

[0053] Step S1: Weigh 100 parts of PET polyester, 25 parts of glass fiber, 5 parts of silane coupling agent, 6 parts of DOPO / phosphorus-containing polyacrylate flame retardant masterbatch prepared in Preparation Example 4 and 3 parts of antioxidant 1010.

[0054] Step S2: In a high-speed mixer, first add glass fiber and silane coupling agent and mix for 5 minutes, then add PET polyester, DOPO / phosphorus-containing polyacrylate flame retardant masterbatch prepared in Preparation Example 4 and antioxidant 1010, and mix for 10 minutes.

[0055] Step S3: adding the mixed materials in step 2 into an extruder, setting the temperature of each section of the extruder to 230° C.-270° C., and extruding to obtain antimony-free, environment-friendly, flame-retardant PET polyester masterbatch.

[0056] Performance Testing

[0057] The antimony-free, environment-friendly, flame-retardant PET polyester masterbatch obtained in Example 1 and Comparative Examples 1-3 was prepared into a 0.8 mm thick strip by an injection molding machine, and the performance was characterized. The tensile strength was tested according to GB / T 1040.2-2006. The vertical flame retardancy of the strip was tested according to UL-94, V0: when the total reburning time of 5 test samples is not longer than 50 seconds, each flame is less than 10 seconds, and no droplets are allowed; V1: when the total reburning time of 5 test samples is not longer than 150 seconds, each flame is less than 30 seconds, and no droplets are allowed; V2: when the total reburning time of 5 test samples is not longer than 150 seconds, each flame is less than 30 seconds, and droplets are allowed; when the test results do not meet the above V0, V1 and V2 standards, the level (nc) is not listed in the following table. The limiting oxygen index was tested according to GB / T2406-93. The test results are shown in Table 1.

[0058] Table 1 Antimony-free environmentally friendly flame retardant PET polyester

[0059] <![CDATA[Tensile strength / MPa > Vertical burning level Oxygen Index Example 1 127.3 UL94V-0 42 Comparative Example 1 124.5 UL94V-1 25 Comparative Example 2 98.7 UL94V-1 36 Comparative Example 3 86.9 UL94V-2 33

[0060] From the comparison between Example 1 and Comparative Example 1, it can be seen that Example 1 has better vertical combustion flame retardant effect and higher oxygen index than Comparative Example 1. This may be because the flame retardant monomer polyphosphorylcholine glycol acrylate is omitted in the shell layer of Comparative Example 1, which increases the burning speed, burning time, flame appearance time and droplet phenomenon of the flame retardant masterbatch, that is, the flame retardant performance decreases.

[0061] From the comparison between Example 1 and Comparative Example 2, it can be seen that Example 1 has higher tensile strength, better vertical combustion flame retardant effect and higher oxygen index than Comparative Example 2. This may be because Comparative Example 2 did not adopt the pre-emulsification semi-continuous seed emulsion polymerization method, and did not obtain the nano-scale core-shell structure flame retardant masterbatch, and could not exert the nano-enhancement effect of the flame retardant masterbatch, and could not exert the sustained release effect, which reduced the anti-dripping effect of the flame retardant masterbatch and the oxygen index.

[0062] From the comparison between Example 1 and Comparative Example 3, it can be seen that Example 1 has higher tensile strength, better vertical combustion flame retardant effect and higher oxygen index than Comparative Example 3. This may be because Comparative Example 3 does not adopt the pre-emulsified semi-continuous seed emulsion polymerization method, and DOPO is not pretreated and modified with maleic anhydride. The double bonds introduced by the modification cannot be polymerized with the acrylate monomers and the flame retardant monomer polyphosphorylcholine glycol acrylate to form covalent bonds, and a core-shell structure is not formed to have a sustained release effect. As a result, DOPO has poor compatibility and dispersibility with the polyester matrix, is prone to droplet phenomenon, and has a reduced flame retardant effect. It is also impossible to exert a nano-enhancement effect through the nano effect, which reduces the tensile strength of the polyester composition.

[0063] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch, the preparation method of which comprises the following steps: Step 1: Add 1-10 g of N-(3-aminopropyl)methylacrylamide hydrochloride and 5-45 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to xylene, react at a temperature of 100-120° C. for 30-50 h, and concentrate, wash, and dry the reaction solution to obtain a DOPO-aminopropylacrylamide intermediate; Step 2, adding 5-25 g of DOPO-aminopropyl acrylamide intermediate and 1-10 g of olefinic acid to xylene, reacting at a temperature of 25-45° C. for 1-3.5 h, and concentrating, washing, and drying the reaction solution to obtain modified DOPO; Step 3, dissolving 0.1-5g SDS in water to form 100mL-500mL of aqueous phase, adding 1-20g of modified DOPO, 1-20g of methyl methacrylate, and 0.01-0.1g of AIBN to 100mL-500mL of acetone to form oil phase 1; then adding 3-30g of methyl methacrylate, 3-30g of styrene, 1-20g of polyphosphorylcholine glycol acrylate, 3-30g of isooctyl acrylate, and 0.1-0.9g of AIBN to 200mL-700mL of acetone to form oil phase 2, adding oil phase 1 to the aqueous phase, stirring and emulsifying to form an oil-in-water emulsion, introducing nitrogen, heating to 70-85°C under stirring for reaction for 1-2h to form a core layer, continuing to drop oil phase 2, dropping it within 2-5h to form a shell layer, cooling to room temperature, filtering, and washing to obtain DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch.

2. The DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch according to claim 1, characterized in that: The particle size of the DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch is 20-150 nm.

3. The DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch according to claim 1, characterized in that: Step 1 comprises 3-10 g of N-(3-aminopropyl)methacrylamide hydrochloride and 10-35 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

4. The DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch according to claim 1, characterized in that: The olefinic acid in step 2 includes one or more of maleic anhydride, itaconic acid and acrylic acid.

5. The DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch according to claim 4, characterized in that: The olefinic acid in step 2 is maleic anhydride.

6. The DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch according to claim 1, characterized in that: Step 2 includes 10-20 g of DOPO-aminopropylacrylamide intermediate and 2-6 g of olefinic acid.

7. An antimony-free, environment-friendly flame-retardant PET polyester, comprising 100 parts of PET polyester, 10-30 parts of glass fiber, 2-12 parts of silane coupling agent, 3-8 parts of DOPO / phosphorus-containing polyacrylate core-shell flame-retardant masterbatch according to any one of claims 1-6, and 1-10 parts of antioxidant 1010.

8. The antimony-free, environment-friendly, flame-retardant PET polyester according to claim 7, characterized in that: The invention comprises 100 parts of PET polyester, 25 parts of glass fiber, 5 parts of silane coupling agent, 6 parts of DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch according to any one of claims 1 to 6 and 3 parts of antioxidant 1010.

9. A method for preparing antimony-free, environmentally friendly flame-retardant PET polyester, the preparation method comprising the following steps: Step S1: weighing the raw material of the antimony-free, environment-friendly, flame-retardant PET polyester according to any one of claims 7 to 8; Step S2: In a high-speed mixer, first add glass fiber and silane coupling agent and mix for 5 minutes, then add PET polyester, DOPO / phosphorus-containing polyacrylate core-shell flame retardant masterbatch according to any one of claims 1 to 6 and antioxidant 1010, and mix for 10 minutes; Step S3: adding the mixed materials in step 2 into an extruder, setting the temperature of each section of the extruder to 230° C.-270° C., and extruding to obtain antimony-free, environment-friendly, flame-retardant PET polyester masterbatch.

Citation Information

Patent Citations

  • Preparation of efficient flame-retardant anti-dripping core-shell particles and polylactic acid material

    CN115260719A

  • Reactive phosphorus-containing flame-retardant monomer, preparation method and application thereof, flame-retardant polyacrylate and preparation method thereof

    CN117447521A